PENGARUH BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Christina Ranty Sumomba; YB. Sigit Hutomo (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2012)
The aim of the study is to provide evidence on how tax rate reform used corporate to affect earningmanagement. The motivation for using deferred tax expense to detect earnings management as there istypically more discretion under generally accepted accounting principles than under tax rules. One mightexpect fi rms to include the reporting of income when there is a pre-announced increasing in the corporate taxrate. It is assumed that managers exploit such discretion to manage income backwards primarily in ways thatdo not affect taxable income. Thus, we expect that decisions to manage earnings backwards will generatebook-tax differences that increase deferred tax expense. Previous studies indicate that deferred tax positionaffects positively on earning management. On the other hand, tax planning and earnings quality jointly affectthe information content of book and taxable income.Sample of 96 manufactured public companies during year 2008-2009 was selected and their fi nancialstatement becomes main data source. Multiple regression model was adopted to analysis the effects of thevariables and the impact of corporate behavior on earning management.The results show that deferred tax expense 2008 signifi cantly positive affects on earning management, butit is not proved in deferred tax expense 2009. This result supports the view that fi rms attempt to shift incomein the period of low rate when there are pre-announced increase changes corporate tax rates. On the otherhand, tax planning is also used to respond increased tax rate to manage earning. Thus, the results support thehypotheses developed.Keywords: Earning management, deferred tax expense, tax planning, tax rate changes, single tax rate.